The effect of welding electrode variations on the mechanical properties of AISI 1018 material using the SMAW process - Saifuddin, Saifuddin; Zaini, Zaini; Putra, M. Adriansyah (Journal of Mechanical Engineering and Fabrication, 2024)
Welding quality is largely determined by welding parameters such as welding current, welding electrode and the type of welding process used. The type of electrode with a certain chemical composition has an impact on the fusion that occurs between the parent material and the welding electrode. so that a study is needed on the effect of electrodes on the quality of the joint. The purpose of this study was to determine the effect of welding electrode variations on the mechanical properties of AISI 1018 material using the SMAW process. The material used in this study was AISI 1018 low carbon steel welded using SMAW welding with hardness and tensile strength testing. The results showed that the highest average hardness value was found in the Weldmetal area found in specimen 1 of the E 7016 electrode, which was 15.33 HRC and E 7018 was 20.20 HRC. The weldmetal area of ​​specimen 2 from electrode E 7016 is 18 HRC and E 7018 is 21.50, The weldmetal area of ​​specimen 3 from electrode E 7016 is 12 HRC and E 7018 is 19.50 HRC and from tensile testing it is known that the average value of raw material is 465.09 Mpa. For welding E 7016 is 492.67 Mpa and E 7018 is 522.79 Mpa